Critical evaluation of the contemporary scholars’ fatwas on substitution of gold dinar for banknotes - Olorogun, L.A; Akhtarzaite Abdul Aziz (Penerbit Universiti Kebangsaan Malaysia, 2021)
Hard currency (‘umlah) plays an essential role in any modern economy. The introduction of money as a means of remuneration successfully eliminated the problems posed by traditional barter trade. Gold and silver became the most widely accepted and circulated form of money in the medieval world, stored in the treasuries of the kings and the wealthy and powerful. In 1971 the US government abolished the Bretton Woods system and exchanged with the floating or fiat economy system which soon became the standard currency system worldwide. Disappointingly, no Muslim government produced legal rulings (fatwas) which rejected the legality of the fiat system and demanded the return to gold and silver backed currency. The single fatwa issued in Saudi Arabia in 1985 concluded that paper currency had completely replaced gold and silver and that all previous Islamic legal rulings issued on gold and silver were now applicable to paper currency. This paper study critically evaluates the 1985 fatwa, questions its legal validity and concludes that only a solid gold and silver currency fulfills the legal requirements of an Islamic currency of which all Muslim economies should adopt and protect.